2014
DOI: 10.1128/jvi.02294-13
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Nipah Virus Phosphoprotein Tetramerization Domain

Abstract: eThe Nipah virus phosphoprotein (P) is multimeric and tethers the viral polymerase to the nucleocapsid. We present the crystal structure of the multimerization domain of Nipah virus P: a long, parallel, tetrameric, coiled coil with a small, ␣-helical cap structure. Across the paramyxoviruses, these domains share little sequence identity yet are similar in length and structural organization, suggesting a common requirement for scaffolding or spatial organization of the functions of P in the virus life cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 49 publications
5
74
1
Order By: Relevance
“…This observation is in agreement with paramyxovirus P oligomerization domains, which also form long coiled coils and are highly thermally stable (Fig. 5B) (28,29).…”
Section: Vp35 Oligomerization Domain Structuresupporting
confidence: 88%
“…This observation is in agreement with paramyxovirus P oligomerization domains, which also form long coiled coils and are highly thermally stable (Fig. 5B) (28,29).…”
Section: Vp35 Oligomerization Domain Structuresupporting
confidence: 88%
“…(A) A water-filled pocket was observed in the center of the NiV P coiled-coil domain toward its N terminus (PDB: 4N5B) (Bruhn et al, 2014). This water pocket is mediated by glycine 519 facing the interior of the coil, which creates empty space.…”
Section: Figure 2 the N-terminal Water Pocketmentioning
confidence: 99%
“…P also contains a central multimerization domain termed the PMD (P multimerization domain). Two crystal structures of this domain have been determined, both of which show that this domain is composed of a long, parallel, tetrameric coiled coil with an a-helical cap structure (Figures 1B and 1C) (Bruhn et al, 2014). This oligomerization domain has been shown to be essential for polymerase function in related viruses (Chen et al, 2006;Moller et al, 2005;Schneider et al, 2004) and was shown to be the L binding site for Sendai virus (SeV), a related paramyxovirus (Bowman et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The P gene produces non-structural accessory proteins known as C, V and W. NiV does not have the hemagglutinin and neuraminidase proteins as other Paramyxoviruses. 20,21 The viral matrix protein (M) of the plasma membrane mediates the contact between the ribonucleoprotein (RNP) complex and the surface glycoprotein, virus particle formation and budding. Replication occurs in cytoplasm.…”
Section: Properties Of Nipah Virusmentioning
confidence: 99%